Correspondence Theory Of Truth: Realisasi Janji Politik Kepala Daerah Terpilih Menuju Lampung Barat Hebat - Padli, Nauril; Darmastuti, Ari; Warganegara, Arizka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2021)
The election of regional heads in the reform era was directly elected by the community, meaning that the election of candidates for regional head candidates was absolutely in the hands of the people. The existence of direct elections has an impact on the various political promises offered by candidates in order to attract voters' sympathy to choose the candidate at the time of the election. This study uses the Correspondence theory of truth, meaning that the researcher wants to find out whether the political promises promised by the regional head candidates at the time of the election have been realized in real terms, can be utilized, felt by the community. Candidates for the elected regional head or regent of West Lampung Regency in the 2017 regional elections, namely pair number (1), Parosil Mabsus and Mad Hasnurin at the time of the campaign offered various work programs or political promises summarized in pitu (seven) superior programs. Therefore, the aim of this research is to find out whether the 7 (pitu) political promise programs of the elected regional heads in the 2017 West Lampung Regency Regional Head Election have been fully realized and to find out the inhibiting factors that have not realized the political promises of the elected regional heads to the Great West Lampung in the Head Election. West Lampung Regency Region 2017. The research method used a qualitative approach, and used interview, observation and documentation data collection tools, while the respondents in this study were policy makers, beneficiaries and observers. The results of this research are: a) The realization of the political promise of the elected regional head of West Lampung Regency for the period 2017-2022, up to 2 (two) years of leadership can be seen from the pitu (seven) political promise programs, there are only 4 programs and 18 activities that are correct. fully realized while 3 (three) programs and 8 (eight) activities that have not been fully realized 2) The inhibiting factor has not been realized the political promise of the elected regional head Towards Great West Lampung in the Regional Head Election of West Lampung Regency 2017 is influenced by 3 (three) factors, namely 1). Limited regional financial capacity of West Lampung Regency, 2) The long processing time and completion of programs and activities and 3) Limited competent human resources in completing programs and activities.